Effects of varenicline on sympatho-vagal balance and cue reactivity during smoking withdrawal: a randomised placebo-controlled trial. Issue 1 (December 2016) - Haarmann, Helge; Gossler, Alexandra; Herrmann, Peter; Bonev, Slavtcho; Nguyen, Xuan; Hasenfuß, Gerd; Andreas, Stefan; Raupach, Tobias
Abstract Background Varenicline is an effective smoking cessation medication. Some concern has been raised that its use may precipitate adverse cardiovascular events although no patho-physiological mechanism potentially underlying such an effect has been reported. The aim of this study was to test the hypothesis that varenicline impacts on sympatho-vagal balance during smoking withdrawal. Methods In this randomised, placebo-controlled trial, muscle sympathetic nerve activity (MSNA), baroreflex sensitivity (BRS), heart rate, and blood pressure were assessed in 17 smokers four weeks before a quit attempt (baseline) and again on the third day of that quit attempt (acute smoking withdrawal). Results Regarding the primary endpoint of our study, we did not find a significant effect of varenicline compared to placebo on changes in MSNA burst incidence between baseline and acute smoking withdrawal (−3.0 ± 3.3 vs.−3.9 ± 5.0 bursts/100 heart beats;p  = 0.308). However, heart rate and systolic blood pressure significantly decreased in the placebo group only, while no significant changes in these parameters were observed in the varenicline group. Exposure to smoking cues during acute withdrawal lead to a significant increase of heart rate in the placebo group, while heart rate decreased in the varenicline group, and the difference in these changes was significant between groups (+2.7 ± 1.0 vs.−1.8 ± 0.5 1/min;p  = 0.002). In all 17 participants combined, a significant increase in heart rate during smoking cue exposure was detected in subjects who relapsed in the course of six weeks after the quit date compared to those who stayed abstinent (+2.5 ± 1.2 vs.−1.1 ± 0.7;p  = 0.018). Six-week abstinence rates were higher in the varenicline group compared to placebo (88 vs. 22 %p  = 0.015). Conclusion We did not find evidence of adverse effects of varenicline on sympatho-vagal balance. Varenicline probably blunts the heart rate response to smoking cues, which may be linked to improved cessation outcome.